World experience of the electric power industry restructuring - Shabalina, L.; Bulavka, E. (Економічний вісник Донбасу, 2017)
The article reveals the factors affecting the electricity consumption in the world. Based on the study of the world experience in the restructuring of the electric power industry, five groups of methods are identified to improve its efficiency: organizational, consolidation of markets, financial, tax and environmental.